Effects of GABAB receptor blockade on lateral habenula glutamatergic neuron activity following morphine injection in the rat: an electrophysiological study - Elahe Amohashemi; Hojjatallah Alaei; Parham Reisi (Wolters Kluwer Medknow Publications, 2023)
Background and purpose: The lateral habenula (LHb), a key area in the regulation of the reward system, exerts a major influence on midbrain neurons. It has been shown that the gamma-aminobutyric acid (GABA)- ergic system plays the main role in morphine dependency. The role of GABA type B receptors (GABABRs) in the regulation of LHb neural activity in response to morphine, remains unknown. In this study, the effect of GABABRs blockade in response to morphine was assessed on the neuronal activity in the LHb. Experimental approach: The baseline firing rate was recorded for 15 min, then morphine (5 mg/kg; s.c) and phaclofen (0, 0.5, 1, and 2 μg/rat), a GABABRs' antagonist, were microinjected into the LHb. Their effects on firing LHb neurons were investigated using an extracellular single-unit recording in male rats. Findings/Results: The results revealed that morphine decreased neuronal activity, and GABABRs blockade alone did not have any effect on the neuronal activity of the LHb. A low dose of the antagonist had no significant effect on neuronal firing rate, while blockade with doses of 1 and 2 μg/rat of the antagonist could significantly prevent the inhibitory effects of morphine on the LHb neuronal activity. Conclusion and implications: This result indicated that GABABRs have a potential modulator effect, in response to morphine in the LHb.